Double pigtail tube drainage for large multiloculated pyogenic liver abscesses - JinHua, Cui; YaMan, Liu; Jian, Li (Frontiers in Surgery, 2023)
Background This study aims to investigate the efficacy and safety of double pigtail tube drainage compared with single pigtail tube drainage for the treatment of multiloculated pyogenic liver abscesses greater than 5 cm. Patients and Methods This study retrospectively analyzed patients with pyogenic liver abscess admitted in the Affiliated Hospital of Chengde Medical College between May 2013 and May 2021. Patients with pyogenic liver abscess more than 5 cm in size, who underwent drainage of the abscess with either double pigtail or single pigtail tube, were included. Results A total of 97 patients with pyogenic liver abscesses larger than 5 cm were studied. These included 34 patients with double pigtail tube drainage and 63 patients with single pigtail tube drainage. The postoperative hospital stay (13.39 ± 4.21 days vs. 15.67 ± 7.50 days; P = 0.045), and time for removal of the catheter (17.23 ± 3.70 days vs. 24.11 ± 5.83 days; P = 0.038) were lower in the double pigtail tube group compared with the single pigtail tube group. The rate of reduction, in three days, of c-reactive protein levels was 26.61 ± 14.11 mg/L/day in the double pigtail tube group vs. 20.06 ± 11.74 mg/L/day in the single pigtail tube group (P = 0.025). The diameter of the abscess cavity at discharge was 3.1 ± 0.07 cm in the double pigtail tube group as compared with 3.7 ± 0.6 cm in the single pigtail tube group (P = 0.047). There was no bleeding in any of the patients despite abnormal coagulation profiles. There was no recurrence of abscess within six months of discharge and no death in the double pigtail tube group. Conclusion: Double pigtail tube drainage treatment in multiloculated pyogenic liver abscesses greater than 5 cm in size, is safe and effective.